PERAN KEBIJAKAN PEMERINTAH DALAM MENGELOLA SUMBER DAYA LAUT INDONESIA - Sultan, Dwiki; Ramadhan, Muhammad Fauzan (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
Indonesia is the largest archipelago in the world with a strategic location. Indonesian waters are vast and hold a lot of potential. The sea is one of the natural forms of water in Indonesia, including lakes, swamps and straits. Indonesia's oceans cover an area of about 5.8 million square kilometres with a coastline of 81,00 kilometres, making it the country with the second longest coastline in the world. This research is descriptive and aims to describe the management of Indonesia's marine resources. With the potential of marine resources that are very promising, the sea and coastal waters in general have functions as global water storage, global climate regulators and accommodate various biological communities, land, and sources of livelihood for the community, especially those living around the sea, coastal areas, and some food products from various marine biota. The management of marine resources in Indonesia must be better and more effective because Indonesia has a vision to make Indonesia a global maritime axis, especially a maritime country that is advanced, sovereign, independent, and strong, and has a personality. The government participates in the management of fisheries resources, both financially and non-financially, which aims for the welfare of the Indonesian people.